PENDEKATAN ACTIVE LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR KUTAGANDOK 2 - Ananda Salsabila Khoirunisa; Tuti Sulastri; Isti Pujihastuti (An-Nizam, 2022)
Successful education will create appropriate and decent human beings in society and will not trouble others. The active learning method is a perspective that considers learning as an activity to build meaning or understanding of experiences and information carried out by the learner, not by the teacher. Motivation is a force or factor contained in humans, which causes, directs, and organizes behavior. The participants of the training for learning motivation and increasing enthusiasm are the 5th grade students of SDN Kutagandok 2 which consists of 31 students. It is hoped that the children will have the motivation and skills to complete various tasks, both school assignments and other tasks. Children get additional insight so that they can change their mindset and have the resilience according to their age growth.